PENGARUH PROGRAM MY TRIP MY ADVENTURE TRANSTV TERHADAP PENGETAHUAN WISATA DI KALANGAN MAHASISWA PROGRAM STUDI USAHA PERJALANAN WISATA (UPW) FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS RIAU - Novia Friska; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The development of the mass media both print and electronic media will bring many changes in society. The most dominant media is television. Private television stations compete to present the best show for the audience. One of them is a documentary program lifestayle My Trip My Adventure served TRANSTV. The theory of S-O-R (Stimulus, Organism, Response) make clear about the effects of mass media is directed, immediately and directly to the communicant. And Cognitive Theory is the use of knowledge or people who use their minds to think.The method used in this research is quantitative descriptive. Data collection techniques in this study using a questionnaire. The total sample for this study as many as 105 respondents and using random sampling techniques. To determine the influence of these two variables, the researchers used a simple linear regression analysis. As for the processing of the questionnaire test, performed using the Statistical Product And Service Solution (SPSS) version of Windows 16.Based on these results with indicators of program variables My Trip My Adventure namely the host, the format of the event, event content, frequency, duration and variable knowledge of travel, namely sensation, perception, thinking, obtained is the regression coefficient in this study is Y = 8.139 + 0.763 X with a 0.00 significance level smaller than α = 0.05. Thus accepted Ha Ho is rejected, meaning that there is the influence of variables program My Trip My Adventure to variable travel knowledge with a contribution of 58.8% moderate category. The percentage shows the effect being included in the program My Trip My Adventure to travel knowledge among students of Business Travel Faculty of Social and Political Sciences of University of Riau.Keywords: program, my trip my adventure, knowledge tour, student Business Travel University of Riau.